Negociação coletiva de servidor público - Resende, Renato de Sousa (2010)
The goal of this work is to discuss on the practice of the collective negotiation in the public service. It s ingrained, in the doctrine and predominant jurisprudence, the understanding that whoever works for the Public Administration doesn't have the ability to exercise the collective right to the collective negotiation, even though they are guaranteed the rights to the labor organization and the strike. The prevalent arguments are that the principle of the supremacy of the public interest, the strict observance at the principle of the legality and the absence of expressed mention in the constitutional text moves away the exercise of this right that possesses, without a doubt, democratic garments and it composes the picture of the public worker's syndical extensive and freedom exercise. Under this intention, they are rebutted, one by one, such arguments, demonstrating: (a) the titularity of the public interests is not, nowadays, state exclusiveness; (b) it doesn t justifies to appeal to a mere legalism, even so it s necessary an observance of a principle of the juridicity, where the normative force of the constitutional principles and the horizontal effectiveness and dimension objectifies of the fundamental rights get stronger; (c) the recognition of the collective negotiation of the public server as fundamental right and implicit constitutional principle, whose implantation duty competes, also, to the Administration. Last, it s been worth the experiences of the Compared Law, of the national initiatives and of the traditional treatment of the theme in the Labour Law for an attempt of conversion of the collective negotiation for the Administrative Law or for its placement as a category belonging to the General Theory of Law